The Antagonist of Retinoic Acid Receptor α, ER-50891 Antagonizes the Inhibitive Effect of All-Trans Retinoic Acid and Rescues Bone Morphogenetic Protein 2-Induced Osteoblastogenic Differentiation - Wang S; Bi W; Liu Y; Cheng J; Sun W; Wu G; Xu X (Dove Medical Press, 2020)
Siqian Wang, 1,* Wenjuan Bi, 2,* Yi Liu, 3,* Jiayi Cheng, 4 Wei Sun, 5 Gang Wu, 4 Xin Xu 1 1Department of Implantology, School and Hospital of Stomatology, Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, Jinan, Shandong Province, People’s Republic of China; 2College of Stomatology, North China University of Science and Technology, Tangshan, Hebei Province, People’s Republic of China; 3Key Laboratory of Oral Medicine, Guangzhou Institute of Oral Disease, Stomatology Hospital of Guangzhou Medical University, Guangzhou Medical University, Guangzhou, People’s Republic of China; 4Department of Oral Implantology and Prosthetic Dentistry, Academic Centre for Dentistry Amsterdam (ACTA), University of Amsterdam (UvA) and Vrije Universiteit Amsterdam (VU), Amsterdam, The Netherlands; 5The Affiliated Stomatology Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gang WuDepartment of Oral Implantology and Prosthetic Dentistry, Academic Centre for Dentistry Amsterdam (ACTA), University of Amsterdam (UvA), Gustav Mahlerlaan 3004, Amsterdam 1081LA, The NetherlandsTel +31 20 5980866Fax +31 20 5980333Email g.wu@acta.nl Xin XuDepartment of Implantology, School and Hospital of Stomatology, Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, No. 44-1, Wenhua Xi Road, Jinan, Shandong 250012, People’s Republic of ChinaTel/Fax +86-531-88382923Email xinxu@sdu.edu.cnBackground: Hypervitaminosis A, alcoholism or medical treatment for acute promyelocytic leukaemia may cause unphysiologically high accumulation of all-trans retinoic acid (ATRA), which could inhibit osteoblastogenesis, thereby triggering osteoporosis. We have shown that bone morphogenetic protein-2 (BMP-2) can only partially antagonize the inhibitive effects of ATRA. In this study, we hypothesized that antagonists of retinoic acid receptors (RARs) could further antagonize the inhibitive effect of ATRA and rescue BMP2-induced osteoblastogenesis.Materials and Methods: We first screened the dose-dependent effects of the specific antagonists of RAR α, β and γ and transforming growth factor-beta receptor (ER-50891, LE-135, MM11253, and SB-43142, respectively) on ATRA-induced inhibition of the total cell metabolic activity and proliferation of preosteoblasts. We selected ER-50891 and tested its effects on osteoblastogenesis with the presence or absence of 1 μM ATRA and/or 200 ng/mL BMP-2. We measured the following parameters: Alkaline phosphatase activity (ALP), osteocalcin (OCN) expression and extracellular matrix mineralization as well as the level of phosphorylated Smad1/5.Results: ER-50891 but not LE-135, MM11253, or SB-431542 significantly antagonized the inhibition of ATRA and enhanced the total cell metabolic activity and proliferation of preosteoblasts. Dose-dependent assays show ER-50891 could also rescue ATRA inhibited OCN expression and mineralization with or without the induction of BMP. ER-50891 also suppressed the ALP activity that was synergistically enhanced by BMP and ATRA. Neither ATRA, nor ER-50891 or their combination significantly affected the level of BMP-induced phosphorylated Smad1/5.Conclusion: The antagonist of RARα, ER-50891 could significantly attenuate ATRA’s inhibitive effects on BMP 2-induced osteoblastogenesis.Keywords: bone morphogenetic protein 2, all-trans retinoic acid, retinoic acid receptor, osteoblastogenesis, transforming growth factor beta